Considering Students’ Reading Interest in Text-Selection to Foster Literacy in the English Classroom - Pustika, Reza (Ahmad Dahlan Journal of English Studies, 2018)
This work is a review paper. This conceptual writing focuses on how students’ reading interest is essential for reading instruction. This argument is derived from some experts who suggest the teachers carry literacy in the classroom. It means that teachers should take students’ interest into account. There are some benefits of considering students’ interest in reading classrooms. In addition, some factors can influence reading activities in the classroom. One of those is the text. Texts serve as the input for the students in reading activities. However, not all texts are appropriate for the students. Therefore, this conceptual study presents some considerations in choosing the texts and ways to take students’ interest into account in reading activities. The considerations in choosing the text are taken and analyzed from some experts who are concern with this topic. Along the way, teachers can finally consider the students’ reading interest by understanding the ways how to consider the students’ interest in selecting the texts that will be used in the English reading classroom proposed by experts.